EVALUASI KEBIJAKAN PELAYANAN ADMINISTRASI TERPADU DI DISTRIK NIMBORAN KABUPATEN JAYAPURA - Sutriman Sutriman; Nur Aedah (Universitas Cenderawasih, 2022)
The purpose of this study is to describe and analyze Integrated administrative services performed by government officials in Nimboran District, Jayapura Regency and to analyze the factors that support and hinder the implementation of Integrated administrative services in Nimboran District, Jayapura Regency. The type of research that will be used in this research is qualitative research. Data collection techniques used in this study were in-depth interviews, active observation, and FGD (Focus Guide Discussion). The results of research on the effectiveness of the PATEN Policy; The implementation of PATEN in the sub-district cannot be separated from the role of the organizers. Communication regarding the PATEN policy is also aimed at the public as the service recipients. Resource; The resources of the PATEN policy in Nimboran District, Jayapura Regency indicate that the PATEN policy has been carried out well with the availability of human resources or implementers at the district office. Bureaucratic Structure; So far, the implementation of PATEN services has been carried out according to the procedures in the service SOP. The implementers at the district level put forward the SOP instructions to apply the principles of transparency and friendliness. Meanwhile, the Supporting and Inhibiting factors of PATEN Policy in Nimboran District, Jayapura Regency, show that there is uniformity in the attitude of the implementers at the district level and obstacles that become obstacles in the implementation of PATEN services in Nimboran District, Jayapura Regency. These obstacles include the lack of implementing human resources, dependence on district heads, the online PATEN application system, geographic location of the area, and public awareness that has not increased regarding the PATEN policy.